Agricultural technology choices for poor farmers in less-favored areas of South and East Asia - Pender, John L. (International Food Policy Research Institute, 2007)
During the past several decades dramatic improvement has occurred in agricultural productivity and livelihoods in South and East Asia, stimulated by the Green Revolution and supported by several other factors. Nevertheless, hundreds of millions of rural people in less-favored environments of this region still live in poverty and received limited benefit from the Green Revolution. To address these problems, alternative technological approaches to the conventional Green Revolution technologies are being advocated to address the problems of poor farmers in less-favored areas of Asia, including low external input and sustainable agricultural approaches, organic agriculture and biotechnology. This paper reviews the literature on agricultural technology options in South and East Asia, drawing conclusions concerning technology strategies to reduce poverty among poor farmers in less-favored areas of this region.; Among the main conclusions of the review are the following:; 1.There is no technology approach that will work in all of the diverse circumstances of South and East Asia.; 2.It is difficult, but not impossible, to identify and promote technologies that will substantially improve the livelihoods of poor people in less-favored areas.; 3.Key requirements for technologies to be taken up by farmers and to have a substantial impact on reducing poverty are that the technology is profitable in a relatively short period of time; does not substantially increase risks; and is consistent with farmers’ endowments of knowledge, management skill, land, labor, and other assets.; 4.New technologies, by themselves, are not sufficient to bring about sustainable rural development and elimination of rural poverty, although they can have a major impact. Effective institutions and a stable and supportive policy environment are also critical.; 5.Effective farmers’ organizations accountable to poor farmers are a critical need for the success of all technologies in reaching the poor. Such organizations are needed to reduce the costs and improve the effectiveness of technical assistance efforts for all technologies, and are particularly important for technologies that require effective collective action and for increasing smallholders’ access to markets for organic and other high value products.; 6.Improved methods of technology dissemination are needed to reach poor farmers in less-favored areas. Top down technology transfer approaches that worked well with simple technology packages do not work as well with complex technologies that have to be adapted to local circumstances based on agro-ecological principles and local conditions.; These lessons should give pause to advocates one particular technological approach as the solution for poor farmers in less favored environments of Asia and elsewhere. What farmers need are not technology dogmas but options that can work in their context, combining what is useful from different approaches. This requires a pragmatic approach to learning what works well where and why. In pursuit of such pragmatic options for farmers, research and development programs should not ignore the potentials of traditional farming practices or intensive Green Revolution type technologies, which are well suited to farmers’ needs in many contexts."" - from authors' abstract.